Analysis Of The Effect Servant Leadership And Organizational Culture On Human Resource Performance With Job Satisfaction As An Intervening Variabel In The Drainage Division Of The Departement Of Water Resources And Highways Service, Surabaya City Govermen - Syahrur Romadhona; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
purpose: The purpose of this study is to examine and analyze the influence of servant leadership and organizational culture on human resource performance with job satisfaction as an intervening variable in the Drainage Division of the Water Resources and Highways Service of Surabaya city Goverment. Methods: This study uses a causal research design with a quantitative approach. The research was conducted at the Water Resources and Highways service office, Drainage Division, Jimerto street no. 6-8, Ketabang Village, Genteng District, Surabaya city, East Java. The population in this study consisted of 94 civil servants and non-civil servants working in the Drainage Division of the Water Resources and Highways service office Surabaya city Goverment. The sampling technique used the census method, so that the number of samples taken was 94 employees of the Drainage Division. Data collection was carried out by distributing questionnaires. The data analysis technique used was SEM (Structural Equation Model) based on Partial Least Square (PLS) version 4.1.1.5. Results: The results of this study prove that servant leadership has no effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, servant leadership has no effect on employee performance, organizational culture has a significant and positive effect on employee performance, and job satisfaction is unable to mediate servant leadership and organizational culture on employee performance. Implications: These findings imply that strengthening organizational culture should be prioritized over servant leadership to enhance job satisfaction and employee performance in public sector organizations.